# If x= -2,y=6 is the solution of equation 3ax + 2ay =6 then find value of b from 2(a-1)+2(3b-4)=4.

2
by KSA

Log in to add a comment

by KSA

Log in to add a comment

3ax + 2ay =6

so, 3 a(-2) + 2a(6) = 6

-6a + 12a =6

6a =6

a =1

put a value in eq. 2(a-1) + (3b-4) =4

so, 2 (1-1) + 2(3b -4 ) = 4

0+ 6b - 8 = 4

6b =4+8

6b = 12

b= 2

X=-2

y=6

3ax+2ay=6

-6a+12a=6

6a=6

a=1

2(a-1)=2a-2=2-2=0

2(3b-4)=6b-8

0+6b-8=4

6b=12

b=2

y=6

3ax+2ay=6

-6a+12a=6

6a=6

a=1

2(a-1)=2a-2=2-2=0

2(3b-4)=6b-8

0+6b-8=4

6b=12

b=2